E-commerce platform acceptance : suppliers, retailers, and consumers - Chan, Hing Kai; Yip, Nick; Lacka, Ewelina (Springer International Publishing, 2014)
This book aims to offer a comprehensive overview of the issues facing organizations when deciding whether to accept e-commerce as a platform for business. It provides a detailed evaluation of how the implementation of e-commerce may affect all parties within the supply chain: suppliers, retailers and consumers. It also compares various opportunities and threats of accepting e-commerce in order to conclude whether it might offer access to a new digital era, or whether it is an uncertain option yielding potential pitfalls. This book helps to reveal existing and future consequences of e-commerce acceptance, which are crucial for business decisions and operations in the present and going forward. It therefore provides a unique insight into emerging e-commerce platform acceptance, and is one of the first to provide a holistic perspective of how each party in the supply chain is affected  by e-commerce acceptance. E-commerce is bringing into view more flexible, effective and efficient ways of conducting business activities among suppliers, retailers and consumers. It is not limited to time and space, and therefore this digital platform has already established for itself a major role in today's world economy. Despite promised benefits however, threats emerge which need to be faced when turning to the virtual marketplace - all of which have to be acknowledged before businesses will shift and adapt to the e-commerce platform. This book is intended for postgraduate students, executive MBA students and researchers interested in information management, marketing, and operations management.